Constructing and Validating Students’ Psychological Contract Violation Scale - Itzkovich, Yariv (Frontiers in Psychology, 2021)
For two and a half decades, psychological contracts are researched mainly in work organizations as drivers of employees attitudes and behaviours, overlooking the importance of understanding the nature of students' psychological contracts in higher education. This study constructs and validates a new scale for measuring students’ perceived psychological contract violations in the context of faculty incivility. A mixed-method approach was applied to study the issue in three phases. First, a qualitative method was used to capture and analyze students’ perceived entitlements, as described by 78 college students, resulting in 37 items or elements identified by students as reflecting their psychological contracts. Second, a sample of 244 students was studied to identify students’ perceptions of violated expectations. In the final phase, items were rephrased as expectations and were given to the third sample of 154 undergraduate college students to determine these expectations' level of fulfilment. Additionally, to ascertain discriminate and convergent validity measures, students were asked about the extent to which they experienced faculty incivility (discriminant validity) and frustration with the quality of interaction with their faculty (convergent validity). From these results, students’ psychological contract violation scale was constructed and validated.